2023
DOI: 10.3390/pr11051469
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Bacteria Communities of a Full-Scale Constructed Wetland Treating the Secondary Effluent after Multi-Years’ Operation

Abstract: Constructed wetlands (CWs) had been widely used to treat the tailwater from sewage treatment plants. However, the enduring effectiveness of CWs was still unclear. Therefore, this study aimed to investigate the chemical oxygen demand (COD), ammonia nitrogen (NH4+-N), and total phosphorus (TP) removal efficiencies (RE) of the Hongze CW (HZ-CW) after multi-years’ operation. The average COD RE were 7.6% and 15.14% in the 4th and 5th year, respectively. The NH4+-N RE was 78.33% and 46.04% in the 4th and 5th year, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Processes 2023, 11, 2781 2 of 16 In addition, the greater water depths in the cells of MCWs contribute to storing and purifying wastewater because there is more space without increasing the land source of MCW systems [9]. Li et al [10] studied 63 MCWs grouped into four kinds depending on various water depths and treatment processes, and the maximum nitrogen removal efficiency was 63.7%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processes 2023, 11, 2781 2 of 16 In addition, the greater water depths in the cells of MCWs contribute to storing and purifying wastewater because there is more space without increasing the land source of MCW systems [9]. Li et al [10] studied 63 MCWs grouped into four kinds depending on various water depths and treatment processes, and the maximum nitrogen removal efficiency was 63.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that assimilation and storage by plants and microbes serve as the primary nitrogen removal pathways in MCWs [5,[16][17][18]. The microbial nitrogen cycle within CWs is driven by nitrogen-related microorganisms, such as heterotrophic denitrification genera, facultative autotrophic denitrification genera, autotrophic denitrification genera, anaerobic ammonium oxidation genera, and nitrification genera [9,19].…”
Section: Introductionmentioning
confidence: 99%